2005
DOI: 10.1677/joe.1.06080
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and IGF-I stimulate the formation of the eukaryotic initiation factor 4F complex and protein synthesis in C2C12 myotubes independent of availability of external amino acids

Abstract: The objective of this study was to investigate the effect of insulin and IGF-I on protein synthesis and translation initiation in C2C12 myotubes in nutrient-deprived Dulbecco's phosphate buffered saline (DPBS). The results showed that insulin and IGF-I increased protein synthesis by 62% and 35% respectively in DPBS, and the effect was not affected by rapamycin, but was blocked by LY294002. Insulin and IGF-I stimulated eukaryotic initiation factor 4E (eIF4E) binding protein (4EBP1) phosphorylation in a dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 44 publications
7
53
0
Order By: Relevance
“…The latter competes with eIF4G for binding to eIF4E: when 4E-BP1 is hypophosphorylated, it tightly binds eIF4E to form the translationally inactive eIF4E/4E-BP1 complex. By contrast, when 4E-BP1 is phosphorylated, eIF4E is released and presumably available for binding to eIF4G (35). eIF4E, together with eIF4G and EIF4A, forms the eIF4F complex, that is crucially involved in mRNA translation (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter competes with eIF4G for binding to eIF4E: when 4E-BP1 is hypophosphorylated, it tightly binds eIF4E to form the translationally inactive eIF4E/4E-BP1 complex. By contrast, when 4E-BP1 is phosphorylated, eIF4E is released and presumably available for binding to eIF4G (35). eIF4E, together with eIF4G and EIF4A, forms the eIF4F complex, that is crucially involved in mRNA translation (34).…”
Section: Discussionmentioning
confidence: 99%
“…eIF4E, together with eIF4G and EIF4A, forms the eIF4F complex, that is crucially involved in mRNA translation (34). Phosphorylation of 4E-BP1 induced by growth factors such as insulin and IGF-I has been shown to depend on the Akt/PI3K/mTOR pathway (35), whereas an Akt-unrelated, mTOR-dependent activation has been proposed to results from increased intracellular amino acid availability (35). In a parallel pathway, the eIF2 complex formed by eIF2·, ß and Á, binds the Met-tRNA to the 40S ribosomal subunit to form the 43S initiation complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PI 3-K/Akt/mTOR and PKC signaling pathways might play a role in increased translational efficiency through these RNA complexes (Angenstein et al, 2002;Wu et al, 2005). Clearly, Akt plays a major role in the regulation of translation through eukaryotic initiation factor 4E (eIF4E)/ binding protein (4EBP1) (Shen et al, 2005). Thus, it is plausible that PI 3-K and PKC signaling are involved in AA-mediated CYP2E1 mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Eif4ebp1 leading to its dissociation from Eif4E has been implicated at least in part in insulin-mediated enhancement of translation and cell growth (57). Similarly, cyclin-dependent kinase inhibitor 1A (Cdkn1a or p21) is a protein that binds to cyclin complexes and inhibits cell cycle progression (58), and its activation is associated with ER stress and apoptosis of ␤-cells (59).…”
Section: Foxo1 Inhibition Protects Islet ␤-Cellsmentioning
confidence: 99%